Asymmetry in the Reaction Function of Monetary Policy in Emerging Economies - Bui, Trung Thanh; Kiss, Gábor Dávid (Public Finance Quarterly, 2020)
The Taylor rule is an important device to study the behavior of the central bank. Conventionally, the Taylor rule is constructed by optimizing a quadratic loss function with the constraint of a linear economic system. Accordingly, the response of interest rate is linear with respect to the sign of inflation gap and output gap. In practice, however, monetary authorities in emerging economies can depart from the linear-quadratic framework. The objective of this paper is to investigate the nonlinearity of the Taylor rule driven by either a nonlinear Phillips curve or an asymmetric preference. We use the generalized method of moments (GMM) method to investigate these asymmetries in twelve emerging economies targeting inflation. The empirical results show that deflation pressure caused by economic recessions has a stronger effect on the interest rate. Moreover, the recession avoidance preference is strong in emerging economies whereas the inflation avoidance preference only emerges in a few emerging economies such as Brazil, Colombia, Hungary, Philippines, and South Africa.